Analisis Konfiksasi Bahasa Madura dalam Karya Sastra Cerpen pada Siswa SMP Muhammadiyah 1 Jember - Sila Rahmatina; Anindya Oktaviona Ervinawati; Adilah Puja Rahmawati; Hasan Suaedi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Language is a communication system used by a group of people to convey thoughts, feelings, and information. Language can be in the form of speech, writing, or sign, and has a structure consisting of vocabulary, grammar, and phonology. Each language has unique characteristics that reflect the culture and history of the user community. The means of communication used by humans to interact, which consists of a system of symbols and sounds that are arbitrary and meaningful. The purpose of this research is to analyze the confixation process in the Madura language contained in the short story